Assistance in the Application of Android-Based Exercise Control in DM Patients - Syahid Amrullah; Jaka Pradika; kharisma Pratama (ABDIMAS: Jurnal Pengabdian Masyarakat, 2024)
Diabetes is a serious chronic disease that occurs when the pancreas does not produce enough insulin (a hormone that regulates blood sugar) or when the body cannot effectively use the insulin that is produced. Physical activity is one of the four pillars of diabetes management, along with education, nutritional therapy, and pharmacotherapy. The goal of this activity is to disseminate information about the implementation of an Android-based Exercise Control application for patients with diabetes mellitus (DM). This activity was conducted on May 17, 2024, involving 32 individuals with DM in the Kopri Health Center working area, Sungai Raya Village, Kubu Raya Regency. The methodology included target group surveys, preparation of facilities and infrastructure, implementation of activities, and evaluation. The results were categorized as good (46.88%), satisfactory (37.50%), and unsatisfactory (15.62%). This indicates that the Android-based Exercise Control Application for DM patients is user-friendly and has the potential to increase the motivation of patients with DM to engage in daily physical activities, thereby helping to maintain stable blood sugar levels and reduce the risk of serious complications such as diabetic foot ulcers.